Comparison of methods to evaluate rice (Oryza sativa) germplasm for tolerance to low temperature at the seedling stage - Sharma, Nirmal; Reinke, Russell; Sacks, Erik J. (MDPI, 2021)
Low temperature stress at the seedling stage is a major constraint to rice (Oryza sativa) production. Previously developed screening protocols typically germinate seed and establish seedlings under warm constant-temperature conditions that are optimal for growth, prior to initiating a constant low-temperature challenge. We developed three controlled-environment protocols mimicking extreme cold boro (winter) seasons based on 25 years weather data from Bangladesh to test the hypothesis that by more closely replicating field conditions, greater information about cultivars could be obtained compared to standard protocols. Root and shoot growth after germination in a Petri dish at 20 °C for three weeks gave similar results as visual scores of transplanted seedlings in a standard five-week protocol. Moreover, transplanted seedlings at the end of the nine-week mimic protocols showed large differences in height and dry biomass, whereas for the standard protocols, growth during the warm pre-treatment substantially masked these genotypic differences. Thus, initial screening of large rice germplasm panels can be most efficiently accomplished with a short-duration germination test at low temperature. However, more effective differentiation of cultivars can be accomplished by measuring transplanted seedling growth from the newly-developed mimic protocols. These results will facilitate the development of improved rice cultivars.